The buckets of money retirement solution the ultimate guide to income for life - Lucia, Raymond J. (Wiley, 2010)
"A proven way to protect your nest egg and financially prepare for retirement Many people head into retirement assuming they will have enough money to live on for the rest of their lives. But when issues such economic disaster come into play, their financial cushion can become so thin that they may have to cut back drastically on their standard of living or go back to work just to survive. Don't let this happen to you! It's time to discard outdated financial strategies and get new ones. Protect Your Buckets of Money provides you with the tips and tools to adapt to today's changing economic landscape and find long-term financial stability. Here, in an easy-to-understand and accessible style, author Raymond Lucia outlines his proven Buckets of Money technique. Outlines a proven approach to protecting your retirement nest egg while growing it in a smart and conservative manner filled with real life examples and a self-assessment section that helps you evaluate your investing style Details a workable plan for both saving and withdrawal of your money To win at the retirement game, you need to know your financial goals, divvy up your money accordingly, and then invest intelligently. With this book as your guide, you'll learn how to achieve both income and growth, while reducing risk."--Provided by publisher
Includes bibliographical references and index. - Print version record
Keywords: Retirement income; Finance, Personal; Revenu de retraite; BUSINESS & ECONOMICS; Personal Finance; Retirement Planning